Peran Digitalisasi Sistem Informasi Akuntansi dalam Meningkatkan Efisiensi Operasional Entitas Bisnis - Anggun Suryani Hasmal; Masyhuri, Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to analyze the role of the digitization of Accounting Information Systems in improving the operational efficiency of business entities through a conceptual literature review approach. The method used is a literature review with a thematic-critical analysis of various relevant scientific literature in the fields of accounting and information systems. The results of the study indicate that the digitization of the AIS through automation, cloud computing, and real-time systems can improve operational efficiency by accelerating the flow of information, reducing recording errors, and lowering operational costs. Additionally, digital systems enhance the accuracy and transparency of financial reports, supporting more effective managerial decision-making. However, the implementation of digitalization still faces challenges such as data security, technological infrastructure limitations, and low human resource readiness. A synthesis of the literature indicates that the success of AIS digitalization is largely determined by the integration of technology and the organization’s overall readiness. Therefore, AIS digitalization is positioned as a strategic instrument in enhancing the efficiency and competitiveness of business entities in the era of digital transformation